Pengaruh Penempatan Kerja, Beban Kerja, dan Motivasi Terhadap Retensi Guru Praktik di Pondok Pesantren Darunnajah Jakarta - Kiki Sundari; Cut Zurnali (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to determine the effect of job placement, workload, and motivation on the retention of practicing teachers at the Darunnajah Islamic Boarding School. Retention of practicing teachers is a crucial issue in the sustainability of education in Islamic boarding schools, so an effective strategy is needed in managing teaching staff. This study uses a quantitative method with a survey approach. The population in this study was 50 practicing teachers at the Darunnajah Islamic Boarding School, who were also used as samples with a saturated sampling technique. Data collection was carried out through questionnaires, and data analysis used multiple linear regression tests to test the effect of each independent variable on the retention of practicing teachers. The results showed that job placement had a positive and significant effect on the retention of practicing teachers, which means that placement that is in accordance with the teacher's competence and interests can increase their tendency to stay. Workload had a negative and significant effect on the retention of practicing teachers, indicating that excessive workload can lead to high turnover rates. Meanwhile, motivation had a positive and significant effect on the retention of practicing teachers, indicating that teachers who are highly motivated are more likely to stay in their jobs. Simultaneously, job placement, workload, and motivation had a positive and significant effect on the retention of practicing teachers.